Youth perception towards Plastic Waste Management in Malaysia / Al'hilmi Ihtifazhuddin Burhanuddin and Muhammad Sufian Suhaimi - Burhanuddin, Al'hilmi Ihtifazhuddin; Suhaimi, Muhammad Sufian (2022)
This study is to examine the level of knowledge, the level of awareness and the level of action taken by youth towards plastic waste management. This study is to determine the relationship between the knowledge, awareness with action of youth towards plastic waste management and the impact of plastic pollution in Malaysia. The research design was decided and unit analysis was carried out with the sample size being taken from the people who belong to the “youth” group, and a student form UiTM Seremban campus. The study was carried out by handing out online questionnaires to the respondents regarding the topic and the results were taken to test the hypothesis. The evaluation of independent variables revealed that our youth are knowledgeable, aware, and committed to plastic waste management, as well as the determination of the relationship between youth knowledge, awareness, and commitment to plastic waste management and the impact of plastic pollution in Malaysia. The majority of respondents demonstrated positive outcomes in terms of awareness, knowledge, action, and the influence of the government's policies and efforts toward a good plastic waste management system. Thus, in order to attain a green environment, Malaysian youth must get actively involved in environmental issues and be equipped with the information and skills to make environmental decisions for themselves and future generations.